Decision-Making Effectiveness and Organizational Commitment Among Islamic Boarding School Educators: A Sequential Explanatory Mixed-Methods Study - Muhammad Ali Basroh; Ferinaldi Ferinaldi; Egi Agustandi (Journal of General Education and Humanities, 2026)
Organizational commitment among educators is essential for the continuity of instructional and residential services in Islamic boarding schools. However, the mechanisms through which managerial decisions shape commitment remain insufficiently explained in pesantren settings, where leadership authority and communal values intersect. This study examined the association between decision-making effectiveness and organizational commitment among educators at Al Munawaroh Tabir Raya Islamic Boarding School, Merangin Regency, Indonesia. A sequential explanatory mixed-methods design was used. Quantitative data from 20 educators were collected through a Likert-type questionnaire and analyzed using descriptive statistics, normality and linearity tests, Pearson correlation, simple linear regression, and coefficient of determination. Interviews, observation, and document review with key informants were used to explain the statistical pattern. Decision-making effectiveness was strongly and positively associated with organizational commitment (r = 0.897, p < 0.001), accounting for 80.5% of the observed variance (R² = 0.805). Qualitative evidence indicated that transparent goal setting, participation in formulating alternatives, and systematic evaluation and follow-up promoted fairness, role clarity, and a sense of belonging. The findings position decision-making effectiveness as a salient correlate of educator commitment and support the formalization of participatory decision procedures and feedback mechanisms in Islamic boarding schools.